Goal-setting
This second issue of Volume 2 of Coaching Science Abstracts reviews 41 articles concerned with goal-setting. This is a topic that is treated very lightly by many coaches and athletes. However, when the impact of goal-setting on performance and participation is realized, it can be deemed worthy of much greater and detailed attention. Goal-setting is a set of skills that involves using goals in particular ways to achieve a variety of effects. The simple erroneous notion that there is only one type of goal-setting and that all an athlete needs is an awareness of its existence is too prevalent in the practices and literature of coaching. This set of abstracts should awaken coaches to the recognition of the importance, scope of effect, and different requirements of the various types of goals that are necessary to produce a more complete sporting experience for and to enhance the performances of athletes.